Extracorporeal photopheresis for GVHD prophylaxis after reduced intensity conditioning allogeneic hematopoietic stem cell transplantation: a prospective multicenter phase 2 study. Issue 2 (1st February 2018) - Michallet, Mauricette; Sobh, Mohamad; Garban, Frederic; Bulabois, Claude Eric; Yakoub-Agha, Ibrahim; Coiteux, Valerie; Dulery, Remy; Rohrlich, Pierre-Simon; Legrand, Faezeh; Clement, Laurence; Praire, Aline; Detrait, Marie; et al.
Abstract: We performed a prospective multicenter phase 2 study to evaluate the safety and efficacy of prophylactic Extracorporeal Photopheresis (ECP) in adult patients with hematological malignancies early after RIC allo-HSCT on day 21 twice per week during the first two weeks and then once per week for the next four weeks for a total of eight ECP courses. A total of 20 patients were included; 10 were males, median age was 60 years. All patients engrafted, 17 (85%) received the total eight ECP courses. There were no adverse effects related to ECP. Seven patients developed acute graft-versus-host disease (GVHD), with 15% grade ≥ II cumulative incidence at day 100. The cumulative incidence of chronic GVHD at 2 years was 22%. The 2 years probability of overall survival (OS) and progression-free survival (PFS) were 84 and 74%, respectively. This study shows encouraging results with low acute and chronic GVHD incidence and no interference with graft-versus-leukemia (GVL) effect.